2011
DOI: 10.1002/adem.201000285
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of NiTi Shape Memory Actuator Performance Through Ultra‐Fine Grained and Nanocrystalline Microstructures

Abstract: Due to their combination of good thermomechanical properties, corrosion resistance, and biocompatibility, nearstoichiometric NiTi alloys are the shape memory alloys (SMAs) that have had the greatest commercial success. [1][2][3][4][5] Their shape memory effect is derived from a diffusionless transformation in the solid state known as the martensitic transformation. On cooling from high temperatures, the material undergoes a transformation from the austenite phase to the martensite phase that begins at the mart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 52 publications
1
27
0
Order By: Relevance
“…After melting and casting the materials were subjected to thermo-mechanical treatments (wire drawing, rolling). All details of our ingot metallurgy processing route have been described in the literature [24,28,31,32]. The compositions of the materials which were investigated in the present study are summarized in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…After melting and casting the materials were subjected to thermo-mechanical treatments (wire drawing, rolling). All details of our ingot metallurgy processing route have been described in the literature [24,28,31,32]. The compositions of the materials which were investigated in the present study are summarized in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…[17]. The large reduction in grain boundary area, dislocations, precipitates and other structures that limit transformation induced plasticity make these coarse grained structures less stable than the ideal nanocrystalline NiTi base metals during thermomechanical cycling [21]. While being a small region of the wire, the substantially different properties of the welded region may have a significant effect on the performance of the welded assembly.…”
Section: Tensile and Thermomechanical Fatigue Testingmentioning
confidence: 99%
“…The sole investigation on a small number of thermal cycles of a welded SMA involved a two-way shape memory effect actuator, which concluded that the effect on the actuator performance was minimal [19]. The same cannot be concluded for the cycle life, which has been shown to be greatly affected by coarse grained microstructures like those in the heat affected and fusion zones of the welded wires [16,17,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of pre-strain or ''training'' has long been recognized in the shape-memory actuator field [9][10][11][12][13][14][15]. These references indicate that there are optimal combinations of thermomechanical processing with subsequent prestraining (straining over that of the application) that tends to stabilize the microstructures for either stress or strain cycling.…”
Section: Introductionmentioning
confidence: 99%